Stanford Ocean Experience Self-Contained Study ... - Levett, Aaron Sanford; Queiroz, Anna C. M.; Bailenson, Jeremy; Fauville, Geraldine; Abeles, Adina (OSF Registries, 2020)
With this project, we are investigating the affordances of Virtual Reality (VR) in education using the Stanford Ocean Acidification Experience (SOAE), a VR piece developed by the Virtual Human Interaction Lab at Stanford University. SOAE is an educational experience that allows participants to experience how the ocean absorb carbon dioxide (CO2) molecules, how a coral reef degrades, and how marine life disappears as the ocean acidifies. Through this VR experience, participants will be able to learn about the causes and the consequences of ocean acidification (OA), as well as actions that can be taken to reduce CO2 emissions. Although research investigating immersive VR applications in multiple areas has been increasing, few studies consider how diverse audiences moderate the effects. Investigating how education works on people that hold different beliefs is important to support effective climate change communication and engagement. Immersive virtual reality products have proven popular in gaming and ...